PECULIARITIES OF DIGITAL TRANSFORMATION IN THE PROMOTING CLIMATE POLICY OF ALTERNATIVE ENERGY ENTERPRISES - Борисяк, Елена (SWorldJournal, 2021)
The transition to secondary processing of resources is a way of optimizing natural resource management and an alternative source of energy. The digitization of socio-economic processes affects the transformation of energy market on the basis of climate-ne